PARTICIPATORY ADMINISTRATION OF SCHOOL ADMINISTRATORS IN UDOMKHONGKHAKHIRI CO-CAMPUS UNDER THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE KHON KAEN - putthakee, kawee; NEELAYOTHIN, AKKHARADET (Journal of Humanities and Social Sciences Mahamakut Buddhist University Isan Campus, 2024)
The purposes of this research were to; 1) Examine the Participatory Administration of School Administrators in Udomkhongkhakhiri Co-Campus under the Secondary Educational Service Area Office Khon Kaen. 2) Compare the perceptions of teachers regarding the Participatory Administration of School Administrators in Udomkhongkhakhiri Co-Campus under the Secondary Educational Service Area Office Khon Kaen, based on the opinions of teaching staff. The sample group consists of 159 teachers. The research will utilize the following tools : Questionnaires Statistical analysis methods including frequency, percentage, mean, standard deviation, t-tests, and analysis of variance (ANOVA). These tools will be employed to gather reliable data and efficiently compare the perceptions of teachers regarding Participatory Administration of School Administrators for effective research analysis. The research findings are as follows: 1) The overall Participatory Administration of School Administrators in Udomkhongkhakhiri Co-Campus under the Secondary Educational Service Area Office Khon Kaen, is at the high level, (with a mean score of 4.50). When considering specific aspects, the Participatory Administration of School Administrators is rated highest in 1 areas: Operational aspect, with a mean score of 4.54. and found that the participatory Administration of School Administrators It is at a high level in 3 areas: Goal setting and communication (with a mean score of 4.50). the planning aspect (with a mean score of 4.49). the responsibility aspect (with a mean score of 4.45).2) Regarding the comparison of Participatory Administration of School Administrators in Udomkhongkhakhiri Co-Campus under the Secondary Educational Service Area Office Khon Kaen, according to the perception of teachers with gender Education level and work experience found that teachers of different genders different educational levels There is no difference in perception. Statistically significant at the 0.05 level and teachers with different work experiences. There are different perceptions. Statistically significant at the 0.05 level.